2012
DOI: 10.3928/01477447-20120123-11
|View full text |Cite
|
Sign up to set email alerts
|

Does Adding Computed Tomography Change the Diagnosis and Treatment of Tillaux and Triplane Pediatric Ankle Fractures?

Abstract: Computed tomography (CT) has been deemed a necessary part of management for Tillaux and triplane pediatric ankle fractures. However, no previously published study has attempted to quantify its usefulness in changing management. Six third-party, blinded orthopedic surgeons (F.A.L., E.N.K., D.M.P., K.J.K., D.S.F., K.A.E.) were randomly assigned to evaluate 24 pediatric Tillaux or triplane fractures with plain radiographs; after 6 months, they were again randomly assigned to evaluate the 24 radiographs plus CT sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…In our study, CT resulted in an increase in operative treatment, with 26% of cases originally assigned nonoperative treatment when using radiographs being changed to operative treatment after reviewing CT. Similarly, in a study of triplane and Tillaux fractures, Liporace et al 15 reported that 13% of cases were changed from nonoperative to operative treatment by the six orthopaedic surgeon raters after reviewing CT. This increase in operative treatment and change in screw placement likely reflect a better understanding of the fracture configuration with CT 30 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, CT resulted in an increase in operative treatment, with 26% of cases originally assigned nonoperative treatment when using radiographs being changed to operative treatment after reviewing CT. Similarly, in a study of triplane and Tillaux fractures, Liporace et al 15 reported that 13% of cases were changed from nonoperative to operative treatment by the six orthopaedic surgeon raters after reviewing CT. This increase in operative treatment and change in screw placement likely reflect a better understanding of the fracture configuration with CT 30 .…”
Section: Discussionmentioning
confidence: 95%
“…Computed tomography (CT) scans have been suggested as a useful and necessary addition to triplane fracture evaluation on the basis of their ability to display fracture lines not visible on radiographs 2,7,8,[11][12][13][14][15][16][17] . Although CT has been investigated for diagnosis and treatment of ankle fractures, previous studies have not directly compared radiographs with CT, have not been specific to triplane fractures, and/or were very small case series.…”
mentioning
confidence: 99%
“…The concern for radiation exposure has been previously addressed, and a standard ankle CT is estimated to be equivalent to the dose received by 0.9 chest radiographs [16]. Especially in fractures involving the joint surface, CT can provide invaluable information and has been shown to change surgical indications as well as surgical strategy [17][18][19][20]. MRIs of the ankle can provide further information to soft tissue structures about the ankle and the health of cartilage [21], but are often prohibitive in price and availability to achieve mainstream use in the treatment of acute ankle fractures.…”
Section: Imagingmentioning
confidence: 99%
“…We also used CT to decide upon and plan operative treatment. Liporace has reported that the use of CT does not significantly change the impression of the amount of displacement per case and further results in patients’ reassignment from non-operative management to operative treatment (Liporace et al 2012). We recommend taking CT scans of suspicious physeal fractures and displaced fractures before operative planning.…”
Section: Discussionmentioning
confidence: 99%